Proyecto de vida y su relación con la construcción de paz - Aldana, Luz Adriana; Ramírez, Luisa Fernanda (Universidad Antonio Nariño, 2024)
This booklet has been designed as a tool for teachers and trainers in the school environment to acquire elements related to the life project in peace building and to develop it with secondary school boys, girls and young people in the training spaces that are provided. consider. With the aim of strengthening the spaces around the chair for peace, this booklet proposes getting closer to the realities of the students, through their bets, their abilities, their fears and ideals of life, as well as being able to make practical the fundamental role of building peace based on the decisions, projections and opportunities that are taken. Below you will find two sections: The first presents the proposed guide of four thematic units to work with students. These units address a specific topic through a structure to be worked on with students in the spaces that are considered relevant, and in the second, which presents a general glossary of the basic concepts related to the topics to be developed. We encourage trainers to focus their efforts on learning, on others, on collective construction and on the experience that both trainers and those in the training process have.